I am having trouble finding the complex Fourier series of $f(x) = x$ and using that complex series to find 1)the real Fourier series of $f(x)$ and 2) the complex and real Fourier series of $h(x) = x^2$.

$$ f(x) = x , -\pi < x < \pi $$

$$ f(x) = \sum_{n = -\infty}^{\infty} C_n e^{-inx} $$


$$ C_n = \frac{1}{2\pi}\int_{-\pi}^{\pi} f(x) e^{-inx} dx $$

Attempt: for $n \neq 0$:

$$ C_n = \frac{1}{2\pi}\int_{-\pi}^{\pi} xe^{-inx} dx $$

$$ C_n = \frac{1}{2\pi} \left[ -\frac{x}{in}e^{-inx} \right]_{-\pi}^{\pi} - \frac{1} {2\pi}\left[ \frac{1}{i^2 n^2} e^{-inx} \right]_{-\pi}^{\pi} $$

$$ C_n = -\frac{1}{2in} \left( e^{-in\pi} + e^{in\pi} \right) + \frac{1}{2\pi n^2} \left( e^{-in\pi} - e^{in\pi} \right) $$

$$ C_n = \frac{i}{n}(-1)^n - \frac{i}{\pi n^2 } \sin(n \pi ) $$

$$ \Rightarrow f = \sum_{n = -\infty}^{\infty} \left( \frac{i}{n}(-1)^n - \frac{i}{\pi n^2 } \sin(n \pi )\right)e^{-inx} $$

Is this $f(x)$ correct? How would I get the real and complex series of $h(x)$ from this? I know to get the real series of f(x) we normally can break the sum into

$$ f = \sum_{n = 1}^{\infty} \left[ \left( \frac{i}{n}(-1)^n - \frac{i}{\pi n^2 } \sin(n \pi )\right)e^{-inx} + \left( \frac{i}{-n}(-1)^{-n} + \frac{i}{\pi n^2 } \sin(n \pi )\right)e^{inx} \right] $$

which gives

$$ f(x) = -\frac{ 2\sin(nx) }{n}\left[ (-1)^n + \frac{\sin(n \pi)}{\pi n}\right] $$

so the real series of $h(x)$ could possibly be computed by evaluating the lengthy $f^2$ expression but is this the only way? How do I then evaluate the complex Fourier series of $h$.


$\sin(n \pi) = 0$ ( Don't know why I couldn't notice this before) so,

$$ f(x) = \sum_{n = 1}^{\infty} -\frac{2(-1)^n \sin(nx) }{n} $$

notice that

$$ h(x) = 2 \int_0^x f(\gamma) d\gamma $$

$$ h = 2 \int_0^x \sum_{n = 1}^{\infty} -\frac{2(-1)^{n} \sin(n \gamma) }{n} d\gamma $$

$$ h = \int_0^x \sum_{n = 1}^{\infty} -\frac{4(-1)^{n} \sin(n \gamma) }{n} d\gamma $$

$$ h = \sum_{n = 1}^{\infty} \frac{4(-1)^{n} ( \cos(nx) - 1 )}{n^2} $$

Constant term is

$$ \sum_{n = 1}^{\infty} \frac{4(-1)^{n+1}}{n^2} $$

Don't know how this can be shown to equaivalent to $\frac{\pi ^2}{3}$

  • $\begingroup$ Regardless of whether this is right or not, you might want to pay some attention to the value of $\sin n\pi$ when $n$ is an integer, and also be a little more careful about what happens when $n=0$ $\endgroup$ Apr 27 '13 at 10:27
  • $\begingroup$ Regarding your last sentence see my edit. $\endgroup$ Apr 28 '13 at 21:49

Note that $\sin(n\pi)=0$, so your coefficients are simply $$C_n = \frac{i}{n}(-1)^n,\quad n\neq 0$$ which results in

$$f(x) = -2\sum_{n=1}^{\infty}\frac{(-1)^n}{n}\sin(nx)$$

Just a hint concerning the coefficients $D_n$ of $h(x)$: First, note that $D_0\neq 0$ because $h(x)\ge 0$. Second, note that $h(x)$ is even, so its series will only have cosine terms. The cosine coefficients will turn out to be

$$a_n = 4 \frac{(-1)^n}{n^2},\quad n=1,2,\ldots$$ Try to verify this result yourself.

  • $\begingroup$ Managed to find a_n, but how do I find the constant term of the h(x) expression? $\endgroup$
    – KillaKem
    Apr 27 '13 at 11:56
  • $\begingroup$ $D_0 = \frac{1}{2\pi}\int_{-\pi}^{\pi}h(x)dx=\frac{1}{\pi}\int_{0}^{\pi}x^2 dx=\frac{\pi^2}{3}$. $\endgroup$
    – Matt L.
    Apr 27 '13 at 12:03
  • $\begingroup$ The value will be $D_0 = \sum_{n = 1}^{\infty} \frac{4(-1)^{n+1}}{n^2}$ but is there a way to continue from there to evaluate the actual constant? $\endgroup$
    – KillaKem
    Apr 27 '13 at 12:12
  • $\begingroup$ Thank you! I don't know why I didn't think of that $\endgroup$
    – KillaKem
    Apr 27 '13 at 12:14
  • $\begingroup$ The best way is to equate this sum with the integral in my previous comment. If you want to try to directly evaluate the sum, check the Basel Problem: en.wikipedia.org/wiki/Basel_problem $\endgroup$
    – Matt L.
    Apr 27 '13 at 12:14

An alternative approach.

  1. Since the Fourier trigonometric series expansion is given by $$ \begin{eqnarray*} f(x) &=&\frac{a_{0}}{2}+\sum_{n=1}^{\infty }\left( a_{n}\cos nx+b_{n}\sin nx\right) \\ a_{n} &=&\frac{1}{\pi }\int_{-\pi }^{\pi }f(x)\cos nx,\qquad n=0,1,2,\ldots \\ b_{n} &=&\frac{1}{\pi }\int_{-\pi }^{\pi }f(x)\sin nx,\qquad n=1,2,\ldots, \end{eqnarray*}\tag{1} $$ we conclude that for $f(x)=x$, $-\pi < x < \pi$, we have $a_{n}=0$ and $$ \begin{equation*} b_{n}=\frac{1}{\pi }\int_{-\pi }^{\pi }x\sin nxdx=2\frac{\sin \pi n-\pi n\cos \pi n}{\pi n^{2}}. \end{equation*}\tag{2} $$ So for $x\in]-\pi,\pi[$ $$ \begin{equation*} f(x)=x=2\sum_{n=1}^{\infty }\frac{\sin \pi n-\pi n\cos \pi n}{\pi n^{2}}\sin nx =\dots \end{equation*}\tag{3} $$ For $x=\pm\pi$ the series $(3)$ converges to $0$.
  2. For $h(x)=x^{2}$ a similar computation in this MSE answer (or in this blog post of mine, in Portuguese) yields $$ \begin{equation*} f(x)=x^{2}=\frac{\pi ^{2}}{3}+4\sum_{n=1}^{\infty }\left( (-1)^{n}\frac{1}{n^{2}} \cos nx\right) ,\qquad x\in \left[ -\pi ,\pi \right]. \tag{4} \end{equation*} $$

ADDED: Answer to

Constant term is $$ \sum_{n = 1}^{\infty} \frac{4(-1)^{n+1}}{n^2} $$

Don't know how this can be shown to equivalent to $\frac{\pi ^2}{3}$

Dirichlet eta function (alternating zeta function) $\eta (s)=\sum_{n=1}^{\infty }\frac{(-1)^{n-1}}{n^{s}}$ can be expressed in terms of the Riemann zeta function $\zeta (s)=\sum_{n=1}^{\infty }\frac{1}{n^{s}}$ $$ \begin{equation*} \eta (s)=(1-2^{1-s})\zeta (s) \end{equation*} $$

Since $\zeta (2)=\dfrac{\pi ^{2}}{6}$, we have that $\eta (2)=\dfrac{1}{2} \zeta (2)=\dfrac{\pi ^{2}}{12}$ and

$$4\sum_{n=1}^{\infty }\frac{(-1)^{n+1}}{n^{2}}=4\eta (2)=\frac{\pi ^{2}}{3}.$$

  • 1
    $\begingroup$ I think you missed a factor 4 before the sum in (4). $\endgroup$
    – Matt L.
    Apr 27 '13 at 11:09
  • $\begingroup$ @Matt Thanks! Fixed. $\endgroup$ Apr 27 '13 at 11:12
  • 1
    $\begingroup$ I was looking to compute h(x) = x^2 from f(x) and not directly, but thanks for giving me the final solution, it gives me something to work towards. $\endgroup$
    – KillaKem
    Apr 27 '13 at 11:52
  • $\begingroup$ @KillaKem OK. You can verify that every function $f$ of the form $f(x)=x^{2p}$, $p=1,2,\dots$ can be extended into a trigonometric series, which can be used to evaluate $\zeta(2p)=\sum_{n=1}^\infty 1/n^{2p}$. $\endgroup$ Apr 27 '13 at 13:09
  • $\begingroup$ I am a bit confused about when we use $ f(x)= \text{series}$ and $ f(x)\text{near equal to series}$. If $ f(x)=x$ needs to be expressed in its fourier series in $ [-\pi,\pi]$, what do we write? $ f(x)=\text{series}$ or $ f(x) \text{near equal to series}$ $\endgroup$
    – Manjoy Das
    May 12 '20 at 11:44

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.